2006
DOI: 10.1002/bip.20594
|View full text |Cite
|
Sign up to set email alerts
|

Unzipping the cuticle of the human hair shaft to obtain micron/nano keratin filaments

Abstract: An attempt has been made to obtain intact individual keratin filaments of various levels from micron cortical, micron macrofibril to nano intermediate filament and polypeptide alpha-helix from the human hair shaft. The feasibility of this initiative has been largely demonstrated by finding that there is a longitudinal seam/zipper on the cuticle of the human hair shaft, which can be unzipped by certain solvents such as performic acid and urea, allowing one to use an anatomical approach to separate intact indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This could be caused by intense conjugation where we are seeing polymer on the surface. If the cuticle had been damaged and the cortex underneath was exposed then the SEM should be similar to that observed by Cao et al 32 which is not the case here. A less severe method was applied by using ammonium thioglycolate ('perming salt') and the SEM is shown in Fig.…”
Section: Resultssupporting
confidence: 73%
“…This could be caused by intense conjugation where we are seeing polymer on the surface. If the cuticle had been damaged and the cortex underneath was exposed then the SEM should be similar to that observed by Cao et al 32 which is not the case here. A less severe method was applied by using ammonium thioglycolate ('perming salt') and the SEM is shown in Fig.…”
Section: Resultssupporting
confidence: 73%
“…To separate cuticle and cortex, mechanical methods such as sonication and chemical methods such as enzyme treatment are well known . Thus, obtained interface structures between cuticle and cortex were investigated, and the following research has been reported:…”
Section: Introductionmentioning
confidence: 99%
“… Cao et al . treated hair with performic acid, urea, SDS and reductant to get an envelope‐like hair, from which the cortex easily separated. It was found that the cuticle can be separated from cortex, whereas it is apparently intact by this unzipping method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cuticle scales containing covalently bonded 18-methyleicosanoic acid (18-MEA), this saturated fatty acid contributes the lubricity to the hair fiber. [18,19] This existence of a thin chemically resistant layer called epicuticle has been known since 1916. [20] The recent investigation identified the epicuticle as being a sharply defined and continuous layer approximately 13 nm thick, covering and protecting the entire outwardly facing intracellular surface of every cuticle layer.…”
Section: Morphological Components Of Hair Shaftmentioning
confidence: 99%